Keluarga sebagai Media Pendidikan Tauhid (Telaah Atas Pemikiran Ismail Raji Al-Faruqi dan Lamya Al-Faruqi) - Bekti Khudari Lantong (Jurnal Ilmiah Iqra', 2011)
Human association has had a long story which three institutions had struggled to dominate. The first is the family, which has blood and heredity for bases. The characteristic it engenders in humans are innate and immutable. Certainly, family-living engenders in humans other characteristics which are acquired through association. These, however, are not necessary. Members born to one family may successfully be brought up as members of another; but the innate characteristic remain unchanged. The family was declared by God an intrinsic order of creation. “O..Humankind, revere your Lord, Who created you of a single soul and created of it its spouse.. It is of God’s providing that He created of yourselves spouses in whom to find quiescene, and established between you love and compassion…that He generated from you and your spouses your children and grandchildren”. Parents, their children and grandchildren, and the love and compassion relation between them, constitute an immutable pattern of God creation. This is the family in its nuclear and extended forms spanning three generations. Islam not only acknowledges it but has girded it with law. Unlike any other social system, the law of Islam articulated the relations of all members of the extended family in order to insure proper functioning of all of them. Marriage and divorce, legitimacy and dependency, earnings and supports, inheritance, and the members’ mutual rights and duties have been detailed by the shari’ah.Keywords: Family, Education, Tauhid (Belief in One Supreme God)